Dynamic Response of Concentrically Braced Steel Frames to Pulse Period in Near-Fault Ground Motions - Tonyalı, Zeliha; Yurdakul, Muhammet; Sesli, Hasan (Fırat University, 2022)
Steel braced frame systems (SBFs) having high stiffness and high strength are commonly utilized due to their resistance to lateral seismic forces in regions with high seismicity. In this study, concentrically braced frames (CBFs) having different bracing configurations are used to obtain the significance of the pulse period associated with near-fault (NF) ground motion by time-history dynamic analysis. Besides, far-fault (FF) ground motions are also used to compare with NF ground motion results according to chancing bracing configurations. To achieve dynamic responses of steel frames with different concentric bracings under NF ground motions, which especially have small, medium, and long pulse periods, 3-story and 4-span CBFs having different bracing configurations were selected as an example. 4 FF and 12 NF ground motions having different pulse durations were chosen to evaluate the dynamic response of concentrically braced frames. The results showed that peak ground acceleration (PGA) could be identified as a key parameter that controls the response of braced frames under FF ground motions. In addition, the ratio of the pulse duration to the first mode period is the dominant parameter when this ratio is only greater than 1.0 under the NF ground motions.
Keywords: Engineering; Mühendislik